STRATEGI DIGLOSIA DAN ALIH KODE DALAM WACANA PERLAWANAN PODCAST GHLAF : ANALISIS VAN DIJK - Kurniawan, Ridho Am; Mardiah, Zaqiatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the linguistic strategies used to build a counter-discourse against the financial myth that “employees are poor” in Arabic digital media. It focuses on an episode of the Ghlaf Podcast titled “لماذا الوَظِيفَةُ هِيَ أَسْرَعُ طَرِيقٍ نَحْوَ الثَّرَاءِ”. By integrating Teun A. van Dijk’s socio-cognitive Critical Discourse Analysis with contemporary Arabic sociolinguistics, this research examines how the speaker uses diglossia (switching between Fusha and ‘Ammiyah) and code-switching to English terms as rhetorical tools. The findings show that these linguistic choices are deliberate. They help construct the speaker's identity as a “modern and accessible expert” while redefining wealth as cash flow stability achieved through regular employment. At the social cognition level, this strategy answers the exhaustion felt by young Arabs regarding unrealistic entrepreneurship narratives amidst the economic changes of Saudi Vision 2030. Theoretically, this study expands the use of van Dijk’s model to spoken digital Arabic discourse, emphasizing how linguistic hybridity acts as an ideological tool to negotiate power in the digital economy.